Post-vaccine humoral immunity status of canines and felines in a focus of canine rabies of wild origin in a Colombian region - Sánchez Bonilla, María del Pilar (2020)
The aim of this study was to determine the post-vaccine response of canines and felines of the municipality of San Sebastián de Mariquita, Colombia, which presented in 2014 a fatal case of canine rabies due to atypical bat variant. A cross-sectional and non-experimental sampling by convenience was carried out on 130 canines and 38 felines from the rural and urban area of ​​the municipality. Blood samples were taken. The anti-rabies antibody titration was done using the ELISA kit (Platelia Rabies II Kit Ad Usum Veterinarium) approved by the OIE for the detection and titration of IgG antibodies against the glycoprotein of the virus. The classification categories (protection status) were established as Protected (> 0.5 IU/ml), Insufficient protection (>0.1 - <0.5 IU/ml) and Unprotected (<0.1 IU/ml). Results showed that 40% (52) of the canines obtained titles corresponding to the protected category, 59% (77) to the insufficient protection category and 1% (1) to the unprotected category. The felines presented a similar percentage distribution among the categories: protected 34% (13), insufficient protection 32% (12) and unprotected 34% (13).